2013
DOI: 10.1063/1.4815874
|View full text |Cite
|
Sign up to set email alerts
|

Raman studies of cation distribution and thermal stability of epitaxial spinel NiCo2O4 films

Abstract: Epitaxial thin films of spinel NiCo2O4 (NCO) grown on MgAl2O4 (001) substrates are reported to exhibit dramatic changes in the magnetic and transport properties with deposition temperature. While films grown at lower temperatures (<450°C) are ferrimagnetic with metallic characteristics, those grown at higher temperatures are non-magnetic and insulating. Detailed polarized Raman spectroscopy studies indicate that the higher temperature films have close to the ideal inverse spinel cation distribution, Co3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 21 publications
11
76
1
Order By: Relevance
“…44 In order to demonstrate the presence of weak Raman peaks in the stoichiometric (Co 1−x Ni x ) 3 O 4 films with x=0.33, an inset with the Raman spectrum of a thicker film (∼ 192 nm) is included in Figure 5. Iliev et al 42 also observed weak and broad peaks for their metallic films grown at low temperatures but obtained sharp peaks for their insulating films grown at high temperatures during their epitaxy studies supporting the idea that ionic disorder is responsible for the low resistivity.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…44 In order to demonstrate the presence of weak Raman peaks in the stoichiometric (Co 1−x Ni x ) 3 O 4 films with x=0.33, an inset with the Raman spectrum of a thicker film (∼ 192 nm) is included in Figure 5. Iliev et al 42 also observed weak and broad peaks for their metallic films grown at low temperatures but obtained sharp peaks for their insulating films grown at high temperatures during their epitaxy studies supporting the idea that ionic disorder is responsible for the low resistivity.…”
Section: Resultsmentioning
confidence: 74%
“…It is understood that the cation distribution can differ significantly from the ideal inverse spinel and varies with the preparation conditions leading to a broad variation of electric and magnetic properties. For example, while Iliev et al 42 obtained a distribution close to that of the ideal inverse spinel for their insulating (Co 2/3 Ni 1/3 ) 3 O 4 films from Raman analysis, the results for the conducting, metal-like films suggested a distribution differing from that. Bitla et al 19 who investigated similar films (epitaxial, on MgAl 2 O 4 ) carried out extensive investigations of the cation distribution by X-ray absorption spectroscopy (XAS) and obtained (Co 43 Another F 2g would be expected at about 522 cm −1 but cannot be identified here due to the interference with a signal from Si.…”
Section: Resultsmentioning
confidence: 95%
“…However, Ni x Co 3−x O 4 has been reported to not be stable at high temperature (>400 • C) especially when the Ni concentration is high [41,42]. Raman scattering was applied to study the structural change of Ni doped Co 3 O 4 at different temperatures.…”
Section: Ni Doping Effect On Catalyst Stabilitymentioning
confidence: 99%
“…[ 26 ] Iliev and co-workers have reported that epitaxial NiCo 2 O 4 fi lms deposited at temperatures lower than 450 °C are ferrimagnetic, and those grown at elevated temperatures are nonmagnetic. [ 5 ] The bulk NiCo 2 O 4 , nanorod NiCo 2 O 4 , and 3 wt% NiO/97 wt% NiCo 2 O 4 nanocomposite have been found to exhibit strong magnetization with a high saturation magnetization (M s ) of 29, ≈26, and 24 emu g −1 , respectively. [25][26][27] On account of these intrinsic properties and other advantages such as their low cost, rich abundance, and environmental friendliness, NiCo 2 O 4 materials have been extensively used in the fi elds of photodetection, [ 28 ] photocatalysis, [ 18 ] supercapacitors, [ 29 ] Li-ion batteries [ 30 ] and metal-air batteries, [ 31 ] fuel cells, [ 32 ] magnetic devices, [ 33 ] fl at-panel displays, [ 12 ] ferrofl uid technologies, [ 34 ] drug delivery, [ 35 ] optical limiters and switches, [ 36 ] infrared transparent conducting materials, [ 24 ] heterogeneous catalysis, [ 16 ] and various electrochemical reactions, for example: Cl 2 evolution, [ 37 ] O 2 evolution (OER), [ 38 ] O 2 reduction reaction (ORR), [ 39 ] H 2 O 2 reduction, [ 40 ] methanol oxidation, [ 41 ] and electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%